2016
DOI: 10.23846/srs007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of education programmes on learning and school participation in low- and middle-income countries

Abstract: About 3ieThe International Initiative for Impact Evaluation (3ie) is an international grant-making NGO promoting evidence-informed development policies and programmes. We are the global leader in funding, producing and synthesising high-quality evidence of what works, for whom, why and at what cost. We believe that high-quality, policy-relevant evidence will help make development more effective and improve people's lives. 3ie in-house systematic reviews 3ie in-house systematic reviews appraise and synthesise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 44 publications
(79 reference statements)
2
105
0
Order By: Relevance
“…3ie publishes a series of Systematic Review Summary reports, which present review evidence structured around the theory of change, and focus more clearly on how the interventions themselves work and the reasons underlying heterogeneity in findings. Examples of these summaries are in Table 1 (De Buck et al 2017;Kristjansson et al 2016;Oya et al 2017;Snilstveit et al 2016;Stewart et al, 2016; 3. Keeping reviews up to date Systematic reviews need to be kept up to date.…”
Section: Fostering Learning By Using Programme Theory and Telling A Gmentioning
confidence: 99%
“…3ie publishes a series of Systematic Review Summary reports, which present review evidence structured around the theory of change, and focus more clearly on how the interventions themselves work and the reasons underlying heterogeneity in findings. Examples of these summaries are in Table 1 (De Buck et al 2017;Kristjansson et al 2016;Oya et al 2017;Snilstveit et al 2016;Stewart et al, 2016; 3. Keeping reviews up to date Systematic reviews need to be kept up to date.…”
Section: Fostering Learning By Using Programme Theory and Telling A Gmentioning
confidence: 99%
“…This strategy allows for the identification of national level reforms by exploiting variation in pre-existing levels of education. This can be a powerful tool for examining the return to free primary education in any number of countries, an area of research highlighted by 3ie (Snilstveit et al, 2016) as an area in which more study is needed. Furthermore, this paper shows strong evidence of a positive return to schooling, even in the presence of large increases in pupil-teacher ratios.…”
Section: Resultsmentioning
confidence: 99%
“…First, the paper presents an application of an identification strategy that can be applied to a number of settings to study national level reforms with a minimal amount of variables needed for identification. Measuring the impact of national level removal of user fees was one of the key categories found to need further study in the 3ie systematic review of education policy (Snilstveit et al, 2016). Second, the paper finds strong evidence of a negative relationship between schooling and fertility, and presents evidence of the pathways through which this relationship exists.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Their "right drivers" included capacity building, pedagogy, and systemic policies (Fullan and Quinn 2016). Attention to pedagogy as the driver of improved learning outcomes (whether at the micro or system level) was reiterated by the findings of the International Initiative for Impact Evaluation's (3ie's) summary review of the impact of education programs, which showed that the largest and most consistent positive effects on learning resulted from programs that used structured approaches to improving pedagogy (Snilstveit et al 2016). The experience in Gauteng Province in South Africa mentioned above also demonstrated the importance of structured approaches to pedagogy, with additional emphasis placed on the institutional infrastructure needed to support those approaches .…”
Section: Introductionmentioning
confidence: 99%